Strategic planning of integrated development in the field of science and technology of the enterprises of the machine-building production; Journal of Physics: Conference Series; Vol. 1327 : Innovations in Non-Destructive Testing (SibTest 2019) - Bortalevich S. I.; Loginov E. L.; Chinaliev V. U.; Soldatov A. I. Aleksey Ivanovich (2019, 2019)
Title screen